Differencirovannye škaly ocenki fiziceskoj podgotovlennosti sportsmenov, specializirujušcichsja v trojnom pryžke - Savvinova, Y. I.; Shadrina, O. V.; Cherkashina, E. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article presents the development of methods for determining at the training stage the general physical fitness of the sports contingent, whose specialization is a triple jump. The developed rating scales are given in tabular form and enable the trainer, by a five-point system, without using additional means, only through pedagogical tests, to collect the reliable information about the physical fitness of the athletes, identify the physical indicators by which they are lagging, determine the available power reserves, and make a forecast of the sports performances for the upcoming season of the competitions. This assessment system was tested in the Republic of Sakha (Yakutia) during the training of the athletes, specializing in triple jump. It made it possible to optimize the control functions aimed at the effectiveness of athletes involved in athletics.